Long noncoding RNA UCA1 promotes cell growth, migration, and invasion by targeting miR‐143‐3p in oral squamous cell carcinoma. (4th March 2020) - Duan, Qingyun; Xu, Mei; Wu, Meng; Zhang, Xiong; Gan, Min; Jiang, Hongbing
Abstract: Background: The long noncoding RNA (lncRNA) urothelial carcinoma‐associated 1 ( UCA1 ) is dysregulated in many types of tumors; however, its role in oral squamous cell carcinoma (OSCC) remains unclear. This study aims to determine the effect of lncRNA UCA1 on OSCC. Methods: Fifty‐six paired OSCC and adjacent nontumorous tissues were collected and the levels of UCA1, miR‐143‐3p, and MYO6 in the tissues were evaluated by qRT‐PCR. In in vitro experiments, cell viability, migration, and invasion were measured by, respectively, performing CCK‐8, wound healing, and transwell assays. The target relationships among UCA1, miR‐143‐3p, and MYO6 were verified by dual‐luciferase assay. Western blot and immunohistochemistry were carried out to determine the protein levels. Xenograft mouse model was established to explore the effects of UCA1 in vivo. Results: Levels of UCA1 and MYO6 were increased significantly in OSCC, while the level of miR‐143‐3p was decreased compared with the adjacent nontumorous tissues. UCA1 promoted OSCC cell growth, migration, and invasion both in vitro and in vivo, while miR‐143‐3p reversed the progression. MYO6 was validated as a target for miR‐143‐3p, and MYO6 overexpression reversed the effects of miR‐143‐3p mimic on OSCC cells. Conclusion: LncRNA UCA1 contributes to the proliferation and metastasis of OSCC cells by targeting miR‐143‐3p and upregulating its downstream gene MYO6 . UCA1 could serve as a promising novel target therapy for treatment of OSCC. Abstract : Our study indicates that the UCA1 expression was significantly elevated in OSCC tissues and cells and was correlated with the metastasis and recurrence of OSCC patients. Moreover, the overexpression of UCA1 markedly promoted OSCC progression in vitro and in vivo by upregulating MYO6 expression as a sponge of miR‐143‐3p.